The ultimate book of pub trivia by the smartest guy in the bar : over 300 rounds and more than 3,000 questions - Rogers, Austin, 1978- (Workman Publishing, 2021)
"Challenge yourself, challenge your friends. Or make it official and host a night of fun, enlightening, and hilarious trivia. The pub quiz is a cultural institution, and bartender Austin Rogers is singularly good at it, not only as the long-time host of a hugely popular New York City quiz night, but also as a 12-time Jeopardy! champion whose earnings of over $400,000 are the seventh highest in the show's history. He knows a whole of just about everything, and he knows how to run an uproariously entertaining quiz night-all of which he shares in this bible of pub trivia. The Ultimate Book of Pub Trivia by the Smartest Guy in the Bar features over 3,000 questions sorted into more than 300 rounds of well-balanced and smartly curated quizzes for hours of amusement with family and friends. The topics include pop culture, sports, history, and pretty much everything else under the sun, including Random Sh*t: Reflecting its clingy proclivity, Bindwood and Lovestone are archaic English names for this plant (Answer: Ivy). Sorted by difficulty level, each page is annotated with did-you-know facts, jokes, and other marginalia, and throughout the book are mini-chapters with fascinating history, legendary bar stories, tips for winning Jeopardy!, and useful advice on how to run your own pub trivia night. It's the perfect gift for trivia lovers, pub regulars, and Jeopardy! fans"--